Saracen strongholds AD 630-1050 the Middle East and Central Asia - Nicolle, David 1944- (Fortress (Osprey Publishing), 2008)
The Islamic world drew upon a myriad of pre-existing styles of fortification, taking Romano-Byzantine, Indian and Chinese ideas to create a highly effective and sophisticated hybrid fortification that was both new and distinctive